2021
DOI: 10.3390/ijms22126288
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD1/PD-L1 Immunotherapy for Non-Small Cell Lung Cancer with Actionable Oncogenic Driver Mutations

Abstract: Anti-PD1/PD-L1 immunotherapy has emerged as a standard of care for stage III-IV non-small cell lung cancer (NSCLC) over the past decade. Patient selection is usually based on PD-L1 expression by tumor cells and/or tumor mutational burden. However, mutations in oncogenic drivers such as EGFR, ALK, BRAF, or MET modify the immune tumor microenvironment and may promote anti-PD1/PD-L1 resistance. In this review, we discuss the molecular mechanisms associated with these mutations, which shape the immune tumor microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 104 publications
(63 reference statements)
0
42
1
Order By: Relevance
“…In addition to EGFR mutation, a multi-omics analysis identified that activating mutations in receptor tyrosine kinases (RTK) genes, such as c-MET mutation or amplification, FGFR1 amplification, human EGFR 2 (HER2) point mutation, and insulin-like growth factor 1 receptor (IGF1R) amplification, are associated with primary resistance to ICIs regardless of PD-L1 expression and TMB [ 21 , 89 ]. The activation of Ras/Raf/MEK/ERK signaling also upregulates PD-L1 expression in NSCLC with activated alterations of RTK genes, although IHC of PD-L1 for these genes alterations was not well studied because of the low frequency.…”
Section: The Association Between Pd-l1 Expression and Efficacy Of Icis In Nsclc With Driver Gene Alterationsmentioning
confidence: 99%
“…In addition to EGFR mutation, a multi-omics analysis identified that activating mutations in receptor tyrosine kinases (RTK) genes, such as c-MET mutation or amplification, FGFR1 amplification, human EGFR 2 (HER2) point mutation, and insulin-like growth factor 1 receptor (IGF1R) amplification, are associated with primary resistance to ICIs regardless of PD-L1 expression and TMB [ 21 , 89 ]. The activation of Ras/Raf/MEK/ERK signaling also upregulates PD-L1 expression in NSCLC with activated alterations of RTK genes, although IHC of PD-L1 for these genes alterations was not well studied because of the low frequency.…”
Section: The Association Between Pd-l1 Expression and Efficacy Of Icis In Nsclc With Driver Gene Alterationsmentioning
confidence: 99%
“…Thus, this oncogenic expedient (69) can be exploited for therapeutic purposes in IPF. Moreover, it has been already reported that, in lung cancer mutations occurring in several oncogenes among which MET, modulate tumor microenvironment and a positive correlation between MET amplification and PDL1 overexpression has been already reported (237,238). Thus, in a context-specific regulation of its expression, MET might become a functional marker of IPF and an actionable target, positively associated to response to ICIs (Figure 2).…”
Section: Rationale For Immunotherapy In Fibrotic Lungmentioning
confidence: 83%
“…RET gene rearrangements are identified in 1–2% of patients with NSCLC and in some of them, high PD-L1 expression coexists (13–50% of patients in small published cohorts) [ 7 , 15 , 16 ]. High PD-L1 expression is an established positive predictive factor for immunotherapy in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The value of immunotherapy, such as anti-PD-1/PD-L1 monotherapy in patients with molecular alterations, is questionable. It is considered to be of lower efficacy, especially in patients with EGFR activating mutations and ALK rearrangements [ 4 , 16 , 17 , 18 ]. There are several theories that could explain the low activity of this type of treatment.…”
Section: Discussionmentioning
confidence: 99%